Structural Differences Influence Biological Properties of Glucosylceramides from Clinical and Environmental Isolates of Scedosporium aurantiacum and Pseudallescheria minutispora - Adriana Caneppa; Jardel Vieira de Meirelles; Rodrigo Rollin-Pinheiro; Mariana Ingrid Dutra da Silva Xisto; Livia Cristina Liporagi-Lopes; Lauro de Souza; Maria Teresa Villela Romanos; Eliana Barreto-Bergter (Journal of Fungi, 2019)
Scedosporium/Lomentospora complex is composed of filamentous fungi, including some clinically relevant species, such as Pseudallescheria boydii, Scedosporium aurantiacum, and Scedosporium apiospermum. Glucosylceramide (GlcCer), a conserved neutral glycosphingolipid, has been described as an important cell surface molecule playing a role in fungal morphological transition and pathogenesis. The present work aimed at the evaluation of GlcCer structures in S. aurantiacum and Pseudallescheria minutispora, a clinical and an environmental isolate, respectively, in order to determine their participation in fungal growth and host-pathogen interactions. Structural analysis by positive ion-mode ESI-MS (electrospray ionization mass spectrometer) revealed the presence of different ceramide moieties in GlcCer in these species. Monoclonal antibodies against Aspergillus fumigatus GlcCer could recognize S. aurantiacum and P. minutispora conidia, suggesting a conserved epitope in fungal GlcCer. In addition, these antibodies reduced fungal viability, enhanced conidia phagocytosis by macrophages, and decreased fungal survival inside phagocytic cells. Purified GlcCer from both species led to macrophage activation, increasing cell viability as well as nitric oxide and superoxide production in different proportions between the two species. These results evidenced some important properties of GlcCer from species of the Scedosporium/Lomentospora complex, as well as the effects of monoclonal anti-GlcCer antibodies on fungal cells and host-pathogen interaction. The differences between the two species regarding the observed biological properties suggest that variation in GlcCer structures and strain origin could interfere in the role of GlcCer in host-pathogen interaction.